IMPLEMENTASI PENDIDIKAN AGAMA ISLAM HUMANISTIK DALAM PEMBELAJARAN BERDIFERENSIASIDI SMP ISLAM SUDIRMAN 2 SALATIGA - Ariany Katrin Suryaningtyas; Mukh Nursikin (STAI Nurul Falah Airmolek, 2024)
This research aims to describe how Humanistic Islamic Religious Education (PAI) is implemented in differentiated learning. Apart from that, this research also wants to know the factors that support and hinder teachers in implementing Humanistic PAI, as well as its impact on differentiated learning.This research uses a qualitative method with a descriptive approach. Data collection was carried out through observation, interviews and documentation. Data sources are divided into two, namely primary data and secondary data. Data analysis involves data reduction, data presentation, and verification.The research results show that Humanistic PAI is a learning process that places humans at the center, respects individual rights, and creates an Islamic learning environment. Teachers can change content, processes, products, and learning environments according to student needs. Supporting factors include student enthusiasm, social media, and learning applications. Meanwhile, the main obstacle is the lack of active participation of some students. The implications of differentiated learning are the fulfillment of students' learning needs, the formation of P5 character, and the recognition of students as lifelong learners with the ability to take initiative, creativity and innovation.